Appropriate learning media for mild mentally impaired students at inclusive vocational schools: A literature review - Anggie Marsyaelina; Sudiyatno Sudiyatno; Ranu Iskandar (Jurnal Pendidikan Vokasi, 2022)
In inclusive vocational high schools, students with mild mental retardation have limited thinking and communication. This limitation needs to be overcome by teachers with aid. Students with mild mental retardation study using learning media to improve their knowledge. This study aims to determine what learning media are appropriate for mild retarded learners of Inclusive Vocational High School. This study is a literature review of documents. There are four stages in writing this literature review: determining research topics and questions, searching for literature, analyzing literature search results, and writing a literature review. The documents are journals, conference proceedings, books, thesis reports, and website pages on the internet. The number of documents analyzed is 32 documents. Learning media that is suitable for students with mild mental retardation can be seen from 1.) The text: i.e., short readings, common words used, not convoluted, Arial or Tahoma fonts with the size of 14 pt, non-italic sentences and underline, adding an illustration like image or table; 2.) The colors of the media take on the hot colors: i.e., red, orange, and yellow; 3.) The types of tests that can be used: i.e. multiple-choice tests, right-wrong choices, yes-no question, crossword, cause-effect, test descriptions, and essay; 4.) The shape of learning media is 3D; 5.) the types of aromatherapy that can be used: i.e. lavender essence, calm, citrus melablend, and Northwoods blend.